Serbian education as a bulk to Benjamin Kallay's identity engineering in Bosnia and Herzegovina - Milošević Borivoje M. (Baština, 2023)
Serbian education in Bosnia and Herzegovina under the Austro-Hungarian occupation developed in specific and complex socio-political circumstances. The entire school policy of the new authorities developed in accordance with their political and strategic interests, primarily the physical and spiritual separation of the occupied provinces from Serbia and the establishment of a new, artificial national and cultural identity. Serbian confessional schools, as guardians of Serbian culture and national identity, were under strong and continuous political pressure from the Austro-Hungarian authorities, which culminated during the First World War. Despite this, closely related to the Serbian Church and the Orthodox clergy, the Serbian schools survived as a strong bulwark against Kale's assimilationist political ideas.